595. LAPAROSCOPIC HELLER'S MYOTOMY WITHOUT FUNDOPLICATION. CURRENT EVIDENCE. (24th September 2022) - Davakis, Spyridon; Liakakos, Theodoros; Sdralis, Ilias; Stratigopoulou, Panagiota; Ntoka, Polyxeni; Giagkos, Christos; Andreas, Alexandrou; Charalabopoulos, Alexandros
Abstract: Achalasia is a rare esophageal motility disorder which affects the esophageal smooth muscle layer, causing absent or spastic peristalsis, and absent or partial lower esophageal sphincter (LES) relaxation with an increased LES tone. Laparoscopic Heller's myotomy is the gold standard surgical therapy of esophageal achalasia. The role of fundoplication to minimize GERD after myotomy is debatable. We studied our experience with Laparoscopic Heller Myotomy Without Fundoplication (LHM) for the treatment of esophageal achalasia. A retrospective analysis of prospectively collected data regarding consecutive patients that underwent LHM without fundoplication for the treatment of esophageal achalasia was conducted. All patients were operated between September 1st 2018 and January 1st 2022. Patients included in this study were adults (>18 years old) without upper age limit. All participants completed a subjective dysphagia score questionnaire, received an Eckardt Score preoperatively, as well as at 6 and 12 months following the myotomy procedure. Patients that were treated with endoscopic dilation POEM or esophagectomy were excluded from the study. Twenty-five patients underwent LHM myotomy without fundoplication during the study period. Median age was 42 years (Range: 25-90 years). Median operative time was 70 min (Range: 60-80 min). There was no conversion. Median length of stay was 2 days (Range: 1-15 days). There was one (n=1) mucosal perforation, in a 28-year-old male patient due to overeating, 4 days post LHM. He was treated with laparoscopic primary suturing. There was n=1 (4%) pathologic GERD noted post-operatively. The Eckardt score decreased from 6.5 ± 1.7 to 0.9 ± 1.4 at 1 month and to a 0.8 ± 1.1 at 12 months. Therapy of esophageal achalasia focuses on decreasing the outflow resistance of the GEJ caused by the dysfunctional LES. LHM is considered as the gold-standard therapy for most achalasia patients. LHM is considered safe and effective, while it has been associated with excellent results regarding the relief of dysphagia. There is a reportedly low incidence of new gastroesophageal reflux symptoms. There is no need for fundoplication following LHM since the incidence of GERD is relatively low.